1989
DOI: 10.1128/jb.171.5.2719-2727.1989
|View full text |Cite
|
Sign up to set email alerts
|

Deletion mutants of the Escherichia coli K-12 mannitol permease: dissection of transport-phosphorylation, phospho-exchange, and mannitol-binding activities

Abstract: We have constructed a series of deletion mutations of the cloned Escherichia coli K-12 mtUA gene, which encodes the mannitol-specffic enzyme II of the phosphoenolpyruvate (PEP)-dependent carbohydrate phosphotransferase system. This membrane-bound permease consists of 637 amino acid residues and is responsible for the concomitant transport and phosphorylation of D-mannitol in E. coli. Deletions into the 3' end of mtL4 were constructed by exonuclease III digestion. Restriction mapping of the resultant plasmids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 47 publications
(43 reference statements)
4
95
0
Order By: Relevance
“…The increase in specific activity to 12.0 nmol min-' nmol-I, compared to the 9.7 nmol min-' nmol-I wild-type Ell"', indicates that the domain carrying His-554 interacts with and influences the activity of the domain carrying the Cys-384. Grisafi et al (1989) observed increased activities in more than half of the deletion mutants in which segments extending from the C-terminus (637) into residue 520 had been deleted; however, since the Ell concentration of their mutants was not determined, quantitative statements could not be made.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The increase in specific activity to 12.0 nmol min-' nmol-I, compared to the 9.7 nmol min-' nmol-I wild-type Ell"', indicates that the domain carrying His-554 interacts with and influences the activity of the domain carrying the Cys-384. Grisafi et al (1989) observed increased activities in more than half of the deletion mutants in which segments extending from the C-terminus (637) into residue 520 had been deleted; however, since the Ell concentration of their mutants was not determined, quantitative statements could not be made.…”
Section: Discussionmentioning
confidence: 95%
“…Figure 2 presents a schematic representation of the dimer protein and shows the residues identified as the two phosphorylated intermediates. His-554, which is located in van Weeghel et al an EIII-like domain (Pas et al, 1988;Grisafi et al, 1989;van Weeghel et al, 1991), receives its phosphoryl group from phospho-HPr and passes it on to the second phosphorylation site, Cys-384. From there, the phosphoryl group is coupled to mannitol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EII"' can be divided into three structural and functional domains, which can be stably expressed, and biochemically and kinetically studied (Stephan & Jacobson, 1986;Stephan et al, 1989;Grisafi et al, 1989;White &Jacobson, 1990;van Weeghelet al, 1991a,c;Lolkemaet al, 1990;Pasetal., 1991). Primary sequences of the E11 single species or EII/EIII pairs indicate that several of these proteins are structurally and evolutionarily related (Ebner & Lengeler, 1988;Saier et al, 1988) and that they all consist of a hydrophobic transmembrane domain (IIC), a hydrophilic EIII-like domain (IIA) containing the P-HPr phosphoryl group accepting site, and another hydrophilic domain (IIB) containing the second phosphorylation site.…”
Section: Discussionmentioning
confidence: 99%
“…Data have been presented showing that the site is localized in the Nterminal half of the protein (Grisafi et al, 1989). The present study focuses on the orientation of the binding site on enzyme 11"" with respect to the two sides of the membrane.…”
Section: "'mentioning
confidence: 98%